Use of moringa oleifera for anemia in pregnant women at wini - Asruria Sani Fajriah; Sunariyah Sunariyah; Riza Tsalatsatul Mufida (Journal of Midwifery and Nursing, 2025)
Untreated anemia in pregnant women can have an impact on fetal development and even death in the mother. North Central Timor Regency, is very rich in Moringa (Moringaoleifera) plants which are well known for their benefits and are very easy to obtain. This study aims to determine the effect of using Moringa leaves on the treatment of anemia in pregnant women at the Wini Health Center. Design of this reseach Analytical observational study with cross sectional approach. By purposive sampling technique obtained a sample of 31 respondents, independent variables eating habits and consumption of tea and the dependent variable anemia. This research is an experimental research (pre-experiment) with a one group pre-post test design. This study only used one group of subjects, measurements were taken before and after treatment. The paired T-Test statistical test was used to determine the relationship between the two variables. The research results showed that after treatment, almost all pregnant women had hemoglobin levels in the normal range (> 11.5 g/dl; 67, 8%) and mild anemia as many as 10 respondents (<11.5g/dl; 32.2%). Analysis using the paired T-Test statistical test resulted in p = 0.000 < 0.05, which means there is an influence of the use of Moringa leaves on the treatment of anemia in pregnant women. Giving Moringa leaves as a preparation or vegetable helps to increase hemoglobin, therefore it is recommended to educate the public about consuming Moringa leaves, especially for pregnant women as an additional supplement besides Fe tablets.